Composición de la comunidad, estructura poblacional y condición reproductiva de roedores en una granja avícola de Costa Rica - Monge Meza, Javier (2018)
Rodents are usually part of livestock production systems. Due to the negative impact they caused it is necessary to implement control programs by determining the species and population status. We studied the rodent community in a poultry farm: Fabio Baudrit Moreno Agricultural Experiment Station, University of Costa Rica, located in La Garita, Alajuela, Costa Rica. During 25 months we made fortnightly samplings in two consecutive periods of 24 hours each, with snap traps in 53 fixed stations located around the sheds and warehouses. We collected three species of rodents: house mouse (Mus musculus, n=115), field rat (Sigmodon hirsutus, n=9) and Norway rat (Rattus norvegicus, n=6). The population structure of M. musculus was defined by a sex ratio of 1,9:1 and a predominance of adults. The 44% of the captured females were pregnant. The litter size ranged from 3 to 7 embryos, with an average of 5,17 embryos / litter. The period of greatest reproductive activity was between June and September.